Systematic computational research dealing with the effect of molecular size, heteroatom substitution and modification site on electronic properties, absorption and charge transfer ability of fused ring electron acceptors - Zhi-Zhou Chen; Xin Pu; Fu-Quan Bai (Next Materials)
ITIC and Y6 are two milestone molecules in the field of organic photovoltaics. The two molecules belong to the family of fused ring electron acceptors (FREAs), which work as a fundamental composition in OSCs. Numerous modification strategies are proposed for ITIC and Y6 recently to further increase the energy conversion efficiency, yet both molecules still exhibit great potential. In this work, we divided the central donor moiety of the two A-D-A type molecules into ‘Core’ and ‘Sides’, which refer to the aromatic rings at the molecular center and the two ends of the central donor moiety, respectively. Most modifications on the backbone can be summarized into conjugation expansion and heteroatom substitution on the two sites. Effects of such modifications were investigated with theoretical calculations on 36 model molecules. We employed density functional theory (DFT) to derive electronic energies and absorption spectra, Marcus-Levich-Jortner formalism is then utilized to obtain parameters related with charge transfer characteristics. In conclusion, for ITIC derivatives, most properties follow a monotonical trend along with the size of ‘Sides’ moiety and an oscillatory one along with size of ‘Core’ moiety. Generally, impact of the ‘Core’ is more significant, and even-numbered ‘Core’ will facilitate absorption, while odd-numbered ‘Core’ will promote electron transport. In addition, heteroatom (N and S) substitution in ITIC derivatives gives rise to a better performance. However, trends in Y6 derivatives were much more implicit. It’s observed that though ‘Core’ expansion will somehow improve the performance, extending ‘Sides’ in a certain manner may not be a feasible strategy, as modified molecules with two additional thiophene rings in the ‘Sides’ show particularly undesirable performance. Our results reveal the effect of FREA molecular structure in OSCs, and may provide guidance to the design of effective photovoltaic functional molecules.